Membaca Sebagai Sarana Mengasa Imajinasi Dan Kreativitas Anak Sekolah Dasar - Fisnawati Fisnawati (Prodi PGSD Unsultra, 2024)
This article discusses the importance of reading activities in developing children's imagination and creativity at the elementary school level. Various types of reading materials such as folk tales, fairy tales, and picture books play an important role in building creative thinking skills and imaginative abilities. This study uses a literature review method to examine the influence of reading on children's cognitive, emotional, and social development. The results of the study indicate that consistent reading activities and with the right approach can be an effective means to hone the potential of children's imagination and creativity.